Implications of heathland management for ant species composition and diversity – Is heathland management causing biotic homogenization?. (February 2020) - Hansen, Rikke Reisner; Nielsen, Knud Erik; Offenberg, Joachim; Damgaard, Christian; Byriel, David Bille; Schmidt, Inger Kappel; Sørensen, Peter Borgen; Kjær, Christian; Strandberg, Morten Tune
Abstract: Maintaining heathland ecosystems in an early successional stage is a major aim of most management regimes, such as harvesting, burning or grazing. However, how these types of management affect important ecosystem engineers such as ants, are poorly understood. We registered the density of ant colonies in managed plots (harvested, burned and grazed) and plots with long succession (so forth unmanaged) across six different dry lowland heath sites. With these data, we investigated how composition and richness varied across management regimes and elucidated the direct effects of management from the indirect effects of environmental covariates. Ant species richness was significantly lower in managed plots compared to unmanaged plots. Harvest and grazing regimes were associated with the lowest richness, while intermediate richness was registered in burned plots. Smallest variation in species composition was found in the harvested, followed by grazed, burned and unmanaged heathlands. There was an overall negative association between abundances of organic mound forming species and all types of management, while non-mound forming species where negatively affected by grazing. In addition, Non- and organic mound forming species were indirectly affected through decreasing vegetation complexity. Only ants with mineral mounds benefitted from grazing and burning, but not from harvesting. To promote ant richness and abundance, we propose to downscale the frequency and intensity of management, as well as designating certain parts of the heathland area for later successional vegetation stages. Highlights: Ants are important ecosystem engineers especially on heathlands. Intense large-scale management significantly reduces species richness of ants. Managed plots are more similar in species composition compared to unmanaged plots. Species with different nesting strategies respond differently to management.